DETERMINAN PENDAPATAN ASLI DAERAH DKI JAKARTA DAN EFEK MODERASI JUMLAH WISATAWAN - Sihar Tambun; Iga Putri Hawani (Jurnal Akuntansi Manajerial (Managerial Accounting Journal), 2017)
This research is about the influence of hotel restaurant tax and entertainment tax on regional pure income with number of tourist as a moderating variable. Hotel restaurant tax and entertainment tax are independent variables in this study. Regional pure income is a dependent variable. The number of tourist is a moderating variable. The method used is purposive sampling. The data used are regional pure income, tax revenue of hotel and restaurant, entertainment tax revenue, and the number of tourist in the period of 2006 until 2015 in DKI Jakarta. The data analysis technique was multiple regression analysis and moderated regression analysis. The results of research showed that:  There was no significant influence of hotel restaurant tax on regional pure income. There was no significant influence of entertainment tax on regional pure income. The simultaneous test showed no significant influence of hotel restaurant tax and entertainment tax on regional pure income. The number of tourist able to moderate the influence of hotel restaurant tax on regional pure income.  The number of tourist unable to moderate the influence of entertainment tax on regional pure income.